Influence of Silver Nanoparticles on Dielectric Properties of Human Blood. (1st June 2022) - Gaur, Mulayam Singh; Saran, Dayal; Sagar, Rohan; Sisodia, Kamlesh; Gaur, Karuna; Indolia, Ajay Pal
Abstract : The dielectric properties of human blood are studied using dielectric spectroscopy. The silver nanoparticles (AgNPs) of 50 nm were chemically synthesized using tri-sodium citrate as a reducing agent. Different amount of AgNPs were mixed carefully in fresh human blood of healthy person. The micrographs of blood were recorded before and after addition of nanoparticles. Micrograph shows the contraction of erythrocytes after injection of AgNPs. The contraction of erythrocytes increases with increase of AgNPs concentration. The observed permittivity, tangential loss, impedance decayed with frequency and then constant at higher frequency range. However, tangential loss and impedance shows S shape characteristics. i) silver nanoparticles directly affects the dielectric parameters of human blood; ii) effects are more relevant at frequencies below the MHz and; iii) the influence on the dielectric parameters is less with low concentration of AgNPs. The experimental finding of this heterogeneous system indicates α, β and Maxwell Wagner type of dispersion control the dielectric properties of whole human blood in the frequency range of 42 Hz to 20 kHz at 30 °C.